A Novel Approach of Ayurveda Towards the Understanding of Shookdhanya Varga (Cereals) and Their Fundamental Characteristics and Health Benefits: A Critical Study - Ankita Sharma,; Yogesh. B. Shinde,; Lekhani S. Sirigoud,; Urmila Shirke,; Jyotsna Yadav, (International Journal of Ayurveda and Pharma Research, 2022)
In order to achieve the healthy life, it is important to follow the first principal of Ayurveda which is Ahara (diet). The importance of Ahara in life is described by Acharaya charak in classical texts, where every aspect of Ahara including its regular intake, different categories has been elaborated aptly. In Charak samhita, Acharya has classified the Ahara in 12 different categories. Among these, Shookdhanya (cereals) is first one. Shashtika (rice) Vrihi (rice), Yava (barley), Godhum (wheat) are categorized under Shookdhanya (cereals). The food of these groups has similar pharmacological properties with Madhur rasa (sweet in taste), Madhur vipak (sweet after digestion) and Vata kaphahar action. According to modern science Shook dhanya dravya are included in monocotyledon and energy giving food. Energy giving food mainly includes cereal groups like wheat, rice, maize (corn), oats, Jowar, Ragi, and Bajra. Here an attempt has been made to study the fundamental characteristics and health benefits of the class of cereals (Shookadhanya group of Ahara).